2018
DOI: 10.1080/07347332.2018.1510869
|View full text |Cite
|
Sign up to set email alerts
|

A randomized pilot trial of a couple-based intervention addressing sexual concerns for breast cancer survivors

Abstract: Purpose: The purpose was to test the feasibility, acceptability, and preliminary efficacy of a 4session couple-based Intimacy Enhancement (IE) intervention addressing breast cancer survivors' sexual concerns delivered via telephone. Design/Sample: Twenty-nine post-treatment breast cancer survivors reporting sexual concerns and their intimate partners were randomized (2:1) to the IE intervention or to an educational control condition, both of which were delivered by trained psychosocial providers. Methods: Feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 47 publications
1
68
0
1
Order By: Relevance
“…Moreover, increases in sexual health communication were not accompanied by decreases in patients' satisfaction, suggesting that clinicians need not worry that discussing sexual health will be off putting to patients. Finally, research has shown that worse sexual problems are associated with worse psychological distress for breast cancer survivors, and that addressing their sexual concerns may reduce psychological distress . Future studies could investigate whether a sexual health communication intervention improves not only patient sexual health and function but also psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, increases in sexual health communication were not accompanied by decreases in patients' satisfaction, suggesting that clinicians need not worry that discussing sexual health will be off putting to patients. Finally, research has shown that worse sexual problems are associated with worse psychological distress for breast cancer survivors, and that addressing their sexual concerns may reduce psychological distress . Future studies could investigate whether a sexual health communication intervention improves not only patient sexual health and function but also psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research has shown that worse sexual problems are associated with worse psychological distress for breast cancer survivors, 31,32 and that addressing their sexual concerns may reduce psychological distress. 33,34 Future studies could investigate whether a sexual health communication intervention improves not only patient sexual health and function but also psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We initially conducted a randomized pilot trial of the IE intervention in a sample of breast cancer survivors and their intimate partners and found support for the intervention's feasibility and acceptability as well as promising effects on key sexual and psychosocial outcomes [55]. We thus planned the current full-scale trial to evaluate the IE intervention's efficacy, investigate mediators of treatment effects, and explore potential intervention moderators.…”
Section: Introductionmentioning
confidence: 99%
“…Cabe mencionar que, aunque se mantienen las mejoras en el tiempo, en el estudio mencionan que se obtienen mejores resultados en parejas jóvenes. Sin embargo, observando los resultados relacionados con las intervenciones en cáncer de mama es más difícil extraer un resumen de la eficacia pues o encontramos una muestra pequeña (Baucom et al, 2009) (16) o algún seguimiento que parece insuficiente (Barsky Reese et al, 2018) (8) , y estos aspectos no nos permiten obtener una conclusión generalizable. A partir del estudio de Manne et al (2017) (10) se menciona algo tan obvio (que a veces olvidamos) pero a la vez tan importante, como es la utilidad de un grupo de apoyo en parejas con mayor malestar emocional o en el lado opuesto, la utilidad de intervenciones más estructuradas en parejas que presentan menos malestar.…”
Section: Participantesunclassified